2000
DOI: 10.1093/jn/130.6.1572
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Consumption of Short-Chain Fructooligosaccharides Does Not Affect Basal Hepatic Glucose Production or Insulin Resistance in Type 2 Diabetics

Abstract: Short-chain fructooligosaccharides (FOS) are prebiotics, which escape digestion in the small intestine and are fermented by the colonic microflora into short-chain fatty acids. Recently, we found that the daily consumption of 20 g FOS decreased basal hepatic glucose production in healthy subjects without any effect on insulin-stimulated glucose metabolism. In this study, we evaluated the effects of the chronic ingestion of FOS on plasma lipid and glucose concentrations, hepatic glucose production and insulin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(91 citation statements)
references
References 27 publications
6
82
1
Order By: Relevance
“…One study reported daily supplementation with 14 g Jerusalem Artichoke concentrate (containing OF) for 12 weeks significantly reduced BMI and % body fat levels (59) , while another reported daily supplementation with 21 g OF significantly reduced BW, fat mass and central fat mass (60) . However, none of the other studies found a significant influence of inulin-type fructan supplementation on BW post-intervention (59,65,66,(68)(69)(70)(71)(72) or on food intake during the intervention (65)(66)(67)(68) .…”
Section: Colonic Delivery Of Scfa To Investigate Appetite Effects Fomentioning
confidence: 92%
See 1 more Smart Citation
“…One study reported daily supplementation with 14 g Jerusalem Artichoke concentrate (containing OF) for 12 weeks significantly reduced BMI and % body fat levels (59) , while another reported daily supplementation with 21 g OF significantly reduced BW, fat mass and central fat mass (60) . However, none of the other studies found a significant influence of inulin-type fructan supplementation on BW post-intervention (59,65,66,(68)(69)(70)(71)(72) or on food intake during the intervention (65)(66)(67)(68) .…”
Section: Colonic Delivery Of Scfa To Investigate Appetite Effects Fomentioning
confidence: 92%
“…Less compelling is anthropometric and food intake data from chronic intervention studies, although these were not the main outcomes of interest for all studies (65)(66)(67)(68)(69)(70)(71)(72) except for two (59,60) . One study reported daily supplementation with 14 g Jerusalem Artichoke concentrate (containing OF) for 12 weeks significantly reduced BMI and % body fat levels (59) , while another reported daily supplementation with 21 g OF significantly reduced BW, fat mass and central fat mass (60) .…”
Section: Colonic Delivery Of Scfa To Investigate Appetite Effects Fomentioning
confidence: 99%
“…Luo et al (1996) were the first to show that 20 g of short chain fructans given for four weeks in healthy subjects decreased basal hepatic glucose production, but had no detectable effect on insulin-stimulated glucose metabolism. In T2DM subjects, no significant modification of glucose homeostasis (plasma glucose level or hepatic glucose production) occurred in prebiotic-treated patients (Luo et al, 2000). In a similar study conducted in hypercholesterolemic patients, fructan-prebiotics reduced the PPI response, but the clinical relevance of this effect remains unclear (Giacco et al, 2004).…”
Section: Prebiotics and Blood Glucose Regulationmentioning
confidence: 98%
“…In type 2 diabetic patients, no significant modification of glucose homeostasis (plasma glucose level, hepatic glucose production) occurred in prebiotics-treated patients [57]. In a similar study conducted in hypercholesterolemic patients, prebiotics (inulin-type fructans) treatment reduced the postprandial insulin response, but the clinical relevance of this effect remained unclear [58].…”
Section: The Gut Microbiota: a Novel Target In The Nutritional Contromentioning
confidence: 99%